Legality of the Public Prosecutor's Amendment to the Charges in the Valencya Case in Karawang - Mohamad Hani Anindito; Wijaya, Emilia Metta Karunia (JUSTISI, 2025)
The aim of this study is to analyze the legality of changes to charges by the public prosecutor during the reply stage in the Valencya case in Karawang, focusing on whether such changes are legally valid and their implications for the Indonesian judicial system. The method of research used is a normative juridical approach, which examines the applicable legal regulations and conducts a case study related to changes in charges at the reply stage. This approach also involves an analysis of relevant legal guidelines and procedures in the context of criminal justice in Indonesia. The novelty of this research lies in the analysis of the prosecutor's discretion in changing charges at the reply stage, something that is rarely studied in Indonesian law. This research provides new insights into the practice of changing criminal charges based on considerations of justice and legal morality. The results of the research show that although changing criminal charges to no charges is unusual, it is legally permissible. This provision is regulated in the Attorney General's Office Law and Guideline Book Number 24 of 2021. The amendment of charges was made because the public prosecutor prioritized the principle of justice over legal certainty, taking into consideration truth, conscience, and the values of God Almighty. The Attorney General conducted a special examination of this case because it was considered controversial and had a broad social impact. The conclusion of this study is that although changes to charges at the reply stage are permitted, clearer legal guidelines are needed to regulate the use of prosecutorial discretion. This aims to maintain a balance between justice and legal certainty, as well as to avoid inconsistencies in the application of the law, so that decisions made remain in line with the principles of fair law.